A randomized study of a smartphone application compared with booklet to improve service user's knowledge of their legal rights. (18th October 2017) - O'Donoghue, B.; Roche, E.; Naji, A.; Daly, R.; Madigan, K.; Cole, I.; Lyne, J.
Abstract : Background: The Mental Health Act 2001 has introduced significant changes to the process of admission to hospital for individuals affected by mental health disorders. This study aimed to determine whether a newly designed smartphone application could result in an improvement in service users' knowledge of their rights compared with the paper booklet. Methods: This was a randomized study conducted in an outpatient and day-hospital in North Dublin. Participants were randomized to receive the information booklet as either a smartphone application or in the paper form. A questionnaire which was scored from 0 to 10 was devised and was completed at baseline and at 1-week follow-up. Results: A total of 42 individuals completed the baseline and follow-up questionnaire and of these, 53.7% were female and the mean age was 38.2 years (s.d. ±13.5). A total of 34.1% had a diagnosis of a psychotic disorder, 29.3% had a depressive disorder and 22% had bipolar-affective disorder. The mean score before the intervention in the total group was 3.5 (s.d. ±2.2) and this increased to 5.8 (s.d. ±2.2) at follow-up. Participants randomized to the smartphone application improving by a mean of 2.5 (s.d. ±2.5), while those randomized to the booklet improving by a mean of 2.3 (s.d. ±2.6), which was not statistically significant. Conclusions: Both forms of the information booklet showed improvement in service users' knowledge of their legal rights. It is possible that each individual will have preference for either a paper form or a smartphone form and this study suggests that both forms should be offered to each individual service user.